Reliability, validity and responsiveness of the Spanish Manchester-Oxford Foot Questionnaire (MOXFQ) in patients with foot or ankle surgery. Issue 1 (March 2016) - Garcés, Juan B. Gerstner; Winson, Ian; Goldhahn, Sabine; Castro, Michael D.; Swords, Michael P.; Grujic, Leslie; Rammelt, Stefan; Sands, Andrew K.
Highlights: The MOXFQ is now validated in Spanish in patients with foot or ankle surgery. The Spanish MOXFQ is a valid, reliable and responsive PROM. Its psychometric properties are comparable to those of the English version. It is more responsive than the SF-36 in patients undergoing foot or ankle surgery. Abstract: Background: The Manchester-Oxford Foot Questionnaire (MOXFQ) has been validated in Spanish for use in patients undergoing foot and ankle surgery. Methods: 120 patients completed the MOXFQ and the SF-36 before surgery and 6 and 12 months postoperative. Surgeons completed the American Orthopaedic Foot and Ankle Society (AOFAS) Clinical Rating System. Psychometric properties were assessed for all three MOXFQ dimensions, and for the MOXFQ Index. Results: The Spanish MOXFQ demonstrated consistency with Cronbach's alpha values between 0.65 and 0.90, and reliability ([ICCs] >0.95). It shows a moderate to strong correlation between the Walking/standing dimension and the related domains of the SF-36 (| r | > 0.6), the AOFAS Ankle-Hindfoot Scale (| r | > 0.47) and Hallux-MTP-IP Scale (| r | > 0.64). Responsiveness was excellent, (effect sizes >2.1). The respective minimal detectable change (MDC90) was 14.18 for the MOXFQ Index. Conclusions: The Spanish version of the MOXFQ showed good psychometric properties in patients with foot and ankle disorders.